The comb-clawed beetles (Coleoptera: Tenebrionidae: Alleculinae) of Iraq: checklist, new records and a new species - Novák, Vladimír; Khudhur, Farhad A.; Purchart, Luboš (Zootaxa, 2026)
A new species of the family Tenebrionidae (Coleoptera), subfamily Alleculinae, subtribe Alleculina Laporte, 1840—Mycetocharina (Mycetocharina) hazarmerdica Novák sp. nov. from Iraqi Kurdistan is described and illustrated, including male genitalia. and compared with habitually similar species Mycetocharina (Mycetocharina) kabateki Novák, 2006. The species Magdanalia iranica (Novák, 2007), Mycetocharina (M.) kabateki Novák, 2006, Prionychus cisteloides Seidlitz, 1896 and Mycetochara (Oculochara) mardinica (Novák, 2022) are reported for the first time from the territory of Iraq. The current list of species and genera of comb-clawed beetles (subfamily Alleculinae) from Iraq is presented.